The Influence of Teachers Professional Competence on Students Learning Interest in Islamic Religious Education Subjects at Al-Mahrusiyah Middle School: Pengaruh Kompetensi Profesional Guru terhadap Minat Belajar Siswa pada Mata Pelajaran PAI di SMP Al-Mahrusiyah - Syirva, Atika Nailah; Subhakti, M. Dimas Arfan Adi; Rohmah, Amirotun Nuzulur (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
This study aims to investigate the influence of teacher professional competence on student learning interest in Islamic Religious Education (PAI) at Al-Mahrusiyah Junior High School. Professional competence is a crucial aspect of a teacher's ability to master classroom learning. PAI, as a subject focused on Islamic teachings and law, requires an appropriate approach to ensure students' understanding. This study employed a quantitative method with a sample of 41 respondents at Al-Mahrusiyah Junior High School, Lirboyo, Kediri. Data collection techniques included questionnaires and data analysis using IBM SPSS Statistics 26. The results showed: (1) The professional competence of PAI teachers at Al-Mahrusiyah Junior High School was classified as good, with 2.4% (1 respondent) categorizing it as high, 92.6% (38 respondents) as moderate, and 4.8% (2 respondents) as low. (2) Student learning interest in PAI was also classified as good, with 4.8% (2 students) categorizing it as high, 87.8% (36 students) as moderate, and 7.3% (3 students) as low. (3) Teacher professional competence has an influence of 85.1% on students' learning interest. Analysis using simple linear regression shows a significance value of 0.000 < 0.05, so there is a significant influence of teacher professional competence on students' learning interest and the research hypothesis is accepted (H1 is accepted and H0 is rejected). The coefficient of determination (R Square) value of 0.851 shows that 85.1% of students' learning interest is influenced by teacher professional competence, while 14.9% is influenced by other factors outside the research. (Penelitian ini bertujuan untuk menyelidiki dampak kompetensi profesional guru terhadap hasil belajar siswa dalam mata pelajaran Pendidikan Agama Islam (PAI) di SMP Al-Mahrusiyah. Kompetensi profesional merupakan aspek penting dalam kemampuan guru menguasai pembelajaran di kelas. PAI sebagai mata pelajaran yang berfokus pada ajaran dan hukum Islam memerlukan pendekatan yang tepat agar siswa dapat memahami materi dengan baik. Penelitian ini menggunakan pendekatan kuantitatif dengan sampel sebanyak 41 responden dari SMP Al-Mahrusiyah Lirboyo Kediri. Teknik pengumpulan data yang digunakan adalah kuesioner, dan analisis data dilakukan menggunakan IBM SPSS Statistics 26. Hasil penelitian menunjukkan: (1) Kompetensi profesional guru PAI di SMP Al-Mahrusiyah tergolong baik, dengan kategori tinggi 2,4% (1 responden), sedang 92,6% (38 responden), dan rendah 4,8% (2 responden). (2) Minat belajar siswa pada mata pelajaran PAI juga tergolong baik, dengan kategori tinggi 4,8% (2 siswa), sedang 87,8% (36 siswa), dan rendah 7,3% (3 siswa). (3) Kompetensi profesional guru berpengaruh sebesar 85,1% terhadap minat belajar siswa. Analisis menggunakan regresi linier sederhana menunjukkan nilai signifikansi 0,000 < 0,05, Oleh karena itu, terdapat dampak yang signifikan dari kompetensi guru profesional terhadap hasil belajar siswa dan hipotesis penelitian (H1 diterima dan H0 ditolak). Nilai koefisien determinasi (R Square) sebesar 0.851 menunjukkan bahwa 85,1% hasil belajar siswa dipengaruhi oleh kompetensi guru profesional, sedangkan 14,9% dipengaruhi oleh faktor lain di luar penelitian.)